Serine protease inhibitors decrease metastasis in prostate, breast, and ovarian cancers - Amiram Sananes; Itay Cohen; Irit Allon; Oshrit Ben‐David; Raghda Abu Shareb; Ksenia M. Yegodayev; David Stepensky; Moshe Elkabets; Niv Papo (Molecular Oncology, 2023)
Targeted therapies for prostate, breast, and ovarian cancers are based on their activity against primary tumors rather than their anti‐metastatic activity. Consequently, there is an urgent need for new agents targeting the metastatic process. Emerging evidence correlates in vitro and in vivo cancer invasion and metastasis with increased activity of the proteases mesotrypsin (prostate and breast cancer) and kallikrein 6 (KLK6; ovarian cancer). Thus, mesotrypsin and KLK6 are attractive putative targets for therapeutic intervention. As potential therapeutics for advanced metastatic prostate, breast, and ovarian cancers, we report novel mesotrypsin‐ and KLK6‐based therapies, based on our previously developed mutants of the human amyloid β‐protein precursor Kunitz protease inhibitor domain (APPI). These mutants, designated APPI‐3M (prostate and breast cancer) and APPI‐4M (ovarian cancer), demonstrated significant accumulation in tumors and therapeutic efficacy in orthotopic preclinical models, with the advantages of long retention times in vivo, high affinity and favorable pharmacokinetic properties. The applicability of the APPIs, as a novel therapy and for imaging purposes, is supported by their good safety profile and their controlled and scalable manufacturability in bioreactors.